Determination of the Content of Nitrogen (N), Phosphorus (P), and Potassium (K) in Pellets from Cakalang fish (Katsuwonus pelamis) Waste Fermented Using Adhesives From Broiler Chicken Feces - Safitri, Iin; H. Abram, Paulus (Jurnal Akademika Kimia, 2023)
Fish offal and broiler faeces are underutilised organic waste; the purpose of this study was to determine the levels of nitrogen (N), phosphorus (P) and potassium (K) contained in the pellets from cakalang fish (Katsuwonus pelamis) waste fermented using adhesive from broiler chicken faeces. Nitrogen levels were determined using a colourimeter, phosphorus levels were determined using a UV-Vis spectrophotometer, and potassium levels were determined using a flame photometer. The results showed that the analysis of nitrogen, phosphorus, and potassium in the pellets from the fermentation of cakalang fish waste obtained an average of 4.2 %, 2.21 %, and 3.85 %, respectively.